Psychological Distress among Pharmacists during Second Wave of Pandemic: A Cross-Sectional Study - Keshav Dhakal; Shobhana Nepal; Pratigya Sapkota (Advances in Pharmacological and Pharmaceutical Sciences)
Background. The outbreak of COVID-19 and subsequent lockdown worldwide have shown a psychological impact among healthcare workers. However, data on the psychological impact among community pharmacists are lacking in the Nepalese context. Aim. This study aimed to assess the psychological distress among community pharmacists during COVID-19 pandemic. Settings and Design. A cross-sectional analytical design was adopted to study the psychological distress of pharmacists working in community pharmacies in Bharatpur. Materials and Methods. Purposive sampling method was used to select 172 community pharmacists. The COVID-19 peritraumatic distress index (CPDI) questionnaire adapted from the Shanghai Mental Health Centre was used to measure psychological distress. Statistical Analysis. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 20. Descriptive statistics (mean, standard deviation, percentage) and inferential statistics (chi-square and logistic regression) were used. Results. Out of 172 respondents, 77.9% were severely distressed while 22.1% were mild to moderately distressed due to COVID-19 pandemic. Mean age of the respondents was 27.81 ± 6.35 years. Logistic regression revealed that having education of bachelor and above (AOR = 4.489, 95% CI: 1.747, 11.539), 8 or more working hours (AOR = 7.633, 95% CI: 2.729, 21.352), being unsatisfied with the job (AOR = 11.524, 95% CI: 3.574, 37.158), and having experience of more than 3 years (AOR = 2.857, 95% CI: 1.060, 7.702) were found significantly linked to severe psychological distress among community pharmacists in Bharatpur. Conclusion. All respondents had suffered from some degree of psychological distress due to the pandemic. Our findings reveal the need for psychological intervention to alleviate psychological distress among pharmacists.